MEWUJUDKAN PENDIDIKAN ISLAM YANG MENYENANGKAN - Mulyono, Mulyono (STAIN Pamekasan, 2010)
Abstract: Learning is most effective when its fun: Learning to be effective if a person in a state of happy, argued Peter Kline as an education expert. Based on these opinions, particularly religious Islamic education for children will be effective when formatted in a fun atmosphere. Applications make fun of religious education can be done through: (a) availability of educators who are intelligent, skilled and able to act as a facilitator of fun, (2) education management and leadership support; (3) build a pleasant atmosphere at all educational components; (4 ) speed and accuracy of educational institutions adapt to various changes in its surroundings, (5) to optimize use of resources available; (6) the implementation of learning with a variety of methods, (7) identify and optimize the intelligence of different children (multiple intelligences ), (8) encourage every self-learners enjoy learning (learning as a necessity and a hobby), (9) develop learning programs with the lag time; (10) to appreciate the capabilities and achievements of students; (11) maintain the motivation and enthusiasm of learners in learning; (12) learning programs are directly associated with real life; (13) pull through cooperation with various relevant parties, and (14) to improve quality in a sustainable manner through habituation, familiarization and education itself.